'I can't stand the noise of it': the figure of the child and the critique of colonialism in Jennifer Kent's the Nightingale. Issue 1 (2nd January 2020) - Faulkner, Joanne
ABSTRACT: The presence in Jennifer Kent's The Nightingale of children, and of violence against them, has so far been little commented upon, as much commentary has focused on the film's depiction of rape and colonial gender relations. Yet key plot points are articulated through violence against a child — and the exclamations at these points by the film's antagonist, Lt. Hawkins, of "shut it up" and "I can't stand the ... noise of it, " indicates a critical role played by representations of children that may be turned against colonial power. This article examines the-role of the child as a site of immanent critique of colonial violence in The Nightingale, in the context of the use of representations of childhood in settler-colonial film and culture more broadly.